Trauma-related guilt as a mediator between post-traumatic stress disorder and suicidal ideation - Chou, Po-Han; Wang, Shao-Cheng; Wu, Chi-Shin; Ito, Masaya (Frontiers in Psychiatry, 2023)
Background: As a mental health issue, suicide is a growing global concern, with patients who have posttraumatic stress disorder (PTSD) being at particularly high risk. This study aimed to investigate whether the link between PTSD and suicidal ideation is mediated by trauma-related guilt. Methods: Data were obtained from Wave 1, Time 1 (November 2016), and Time 2 (March 2017) of the National Survey for Stress and Health (NSSH) in Japan. The NSSH is an online longitudinal survey conducted on Japan’s national population aged 18 years and older. The cumulative response rate of the survey was 66.7% at Time 2. A total of 1005 patients with PTSD were included for analyses. The severity of PTSD symptoms was assessed with PTSD DSM-5 Checklist, and the trauma-related guilt were assessed using the two subscales (hindsight-bias/responsibility and global guilt scale) of the trauma-related guilt inventory (TRGI). Suicidal ideation was evaluated using the suicidal ideation attributes scale (SIDAS). Pearson’s correlation was used to investigate the associations among PTSD symptoms, TRGI scores, and SIDAS scores. Causal mediation analysis was applied to evaluate the causal relationship between PTSD, trauma-related guilt, and suicidal ideation. Results: Pearson’s correlation did not show patients’ age, gender, and household income significantly associated with SIDAS scores. On the other hand, severities of PTSD symptoms (r=0.361, p<0.001) and trauma-related guilt (r=0.235, p < 0.001) were positively associated with SIDAS scores. After adjusting for age, gender, and household income, the mediation analysis revealed that trauma-related guilt significantly mediates the effects of PTSD symptoms on suicidal ideation. Conclusions: Our results implied that trauma-related guilt may represent a critical link between PTSD and suicidal ideation, which may be a noteworthy target for therapeutic intervention.